Sealing ability of hydroxyapatite as a root canal sealer: in vitro study - Witjaksono, Widowati; Ab Rani, Samsudin; Naing@Sadiq, Lin@Mohd Ayub (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2004)
occupied by pulp tissue.Gutta-percha is used with various techniques for obturation of the root canal system, and If combine- with lateral condensation remain the most widely accepted and used obturation technique.The most common cause of failure Involving endodontic treatment can be attributed to the lack of an apical seal leading to leakage at the apex. Hydroxyapatite (HA) is the most thermodynamically synthetic calcium phosphate ceramic, and has indicated useful as a sealer because can seal a furcation perforation, Is shown to be biocompatible and also has potential to promote the healing of bone In endodontic therapy. The objective of this study is to detennlne the sealing ability of HA produced by School of Engineering, Unlversiti Sains Malaysia (USM) when used as a sealer in root canal obturation. compare with Tubll-seal ( Zinc-Oxide base ) and Sealapax ( Caldum Hydroxyde base ) sealers. ~ Forty five single rooted human extracted anterior teeth were instrumented and randomly divided Into three experimental groups of 15 teeth each. All teeth in the experimental groups were obturated with later$11y condensed gutta percha technique. Teeth In the first group were sealed using Zinc-Oxide (ZnO) based sealer and those of second group using Calcium Hydroxide (CaOH) based root canal sealer. Third experimental group was sealed using HA from School of Engineering,USM. Teeth were then suspended in 2% methylene blue. After this, teeth were demineralized dehydrated and cleared. Linear dye penetration was detennined under magnifying tense with calibrated eye piece. Statistical analyses of the linear dye pene~tion were performed with Kruskal Wallis test. hJ for the Inter group comparison between HA and ZnO groups and between HA and C&OH groups were analysed by Mann-Whitney test. The resuHs showed that dye penetration for group which were sealed with HA exhibited the lowest penetration and It showed that there was a statistically significant difference both between HA and ZnO groups and also between HA and CaOH groups (p<0.001). We conclude that value added HA based endodontic material which were produced by USM can be used as a root canal sealing materials when It used In combination with epoxy resin since it leaked comparatively less as compared to ZnO and CaOH sealers. Before reaching a definitive conclusion. this material requires further extensive exploration both clinically and In vitro .